L’altro altrimenti possibile: sul pensare contro se stesso. Un dialogo tra Primo Levi e Theodor W. Adorno - Distaso, Leonardo (Bollettino Filosofico, 2019)
In the time between If This is a Man and The Drowned and the Saved, Primo Levi becomes aware of how much he has been a witness of the failure of culture, the failure of which Auschwitz represents its emblem. The present reconstructs some pages of Levi – pages of testimony those of 1947, pages of reflection those of 1986 – and interprets them in the development of critical theory elaborated by Horkheimer and Adorno during the 1930s and the mid-1940s. Horkheimer’s refusal of Hegelian reconciliation of subject and object (I and Other) in the identity of the State and of the bourgeois Kultur – refusal that leads Horkheimer first to clarify the current state of the philosophy of society (1931) and then to elaborate a critical and philosophical theory of society, which is capable of analyzing the betrayal of bourgeois (instrumental) reason and of the authoritarian state (1937) – presents an important implication in the analysis of anti-Semitism and in the explanation of National Socialism, as historical expressions of the catastrophe of reconciliation. This, together with Adorno’s subsequent reflections on the failure of Kultur, his many questions about the meaning of post-Auschwitz, his questions about ideological reification as a reaction of the false conscience with respect to failure, to his investigation into the liquidation of individual as a nullification of the logic of recognition of the I and of the Other, can be an important contribution to the reflection, that not only accompanies those of Levi, but may be able to respond to some of its requests unmasking, at the same time, the hypocrisy and the falseness of the self-preservation of a subjectivity that has nullified the Otherness in an apparent conciliation. Keywords: Reason, Kultur, Conciliation, Barbarism Auschwitz